Ultrasound Presentation of a Disseminated Fetal and Neonatal Rhabdoid Tumor. (31st January 2018) - Joueidi, Yolaine; Rousselin, Aline; Rozel, Céline; Loget, Philippe; Ranchere Vince, Dominique; Odent, Sylvie; Bourdeaut, Franck; Lavoue, Vincent; Le Lous, Maela
Abstract : This is a case report of a disseminated fetal rhabdoid tumor discovered at 32 weeks of gestation in a 29-year-old woman on immunosuppressive therapy. The mother consulted for a decrease in fetal movement. Fetal ultrasound showed signs of a disseminated tumor affecting the left armpit, liver, spleen, and limbs. A caesarian section was performed because of signs of fetal distress. Immunohistochemical analysis of a fetal biopsy showed deletion of the SMARCB1 gene. Pathological analysis of the placenta showed a rhabdoid tumor invading both fetal and maternal compartments. The mother underwent a whole-body MRI, and no metastasis was found. To the best of our knowledge, this is the first report of a disseminated rhabdoid tumor invading both fetal and maternal compartments.